Katedra na Wawelu w XV wieku .......... 11 - Zych, Ewelina (Graduał wawelski (Kraków, AiBKKK, Ms 45): Studium przypadku, 2025)
THE WAWEL CATHEDRAL IN THE 15TH CENTURYThis article presents the history of the Wawel Cathedral in the 15th century. In this century the Jagiellonians sat on the Polish throne, and in the history of the Church these were the times of, among others, Cardinal Zbigniew Oleśnicki and Jan Długosz. It discusses how the appearance of the Wawel Cathedral changed during this century. It was largely influenced by foundations made by representatives of the ruling family, the wealthy, and the clergy. The 15th century was the time of the foundation of the Holy Trinity Chapel and the Chapel of the Holy Cross, the Hinczy Chapel and the construction of a new treasury, and the erection of new altars. It was the time of the great triumph of the Battle of Grunwald, after which the flags captured from the Teutonic Knights were brought to the cathedral. It was a time of several coronations, funerals, episcopal consecrations... It was a time when works by outstanding artists appeared in the cathedral; suffice it to say the tombstones of kings Władysław Jagiełło and his son Kazimierz Jagiellończyk. It was from the mid-15th century that the bishops of Krakow were obliged to donate a golden chalice to the cathedral treasury. In addition, the cathedral was enriched by other works of art in this century, such as reliquaries. They came from royal, episcopal and canonical foundations.... The article also presents the milieu of the cathedral clergy, which consisted of representatives of the Krakow Cathedral Chapter and members of the lower colleges. From the first quarter of the 15th century, the chapter held its sessions in the new chapter-house, located on the ground floor of the Clock Tower. The cathedral’s archives and library were inextricably linked to the cathedral, where books and documents were collected that now enable us to learn about the history of the cathedral and the people associated with it.